2008
DOI: 10.1016/j.neuron.2008.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Differential Neural Activation for Updating Rule versus Stimulus Information in Working Memory

Abstract: Summary Establishing what information is actively maintained in working memory (WM) and how it is represented and controlled is essential to understanding how such information guides future behavior. WM has traditionally been investigated in terms of the maintenance of stimulus-specific information, such as locations or words. More recently, investigators have emphasized the importance of rules that establish relationships between those stimuli and the pending response. The current study used a mental arithmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 37 publications
7
45
1
Order By: Relevance
“…The preferential involvement of SPL in item processing is consistent with earlier work in our lab (Montojo and Courtney 2008) and with its known role in directing spatial attention (Yantis et al 2002). [It is likely that the SPL is involved in relational (and rule) encoding as well as item but to a lesser extent, because relational information can be converted into an abstract format.]…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The preferential involvement of SPL in item processing is consistent with earlier work in our lab (Montojo and Courtney 2008) and with its known role in directing spatial attention (Yantis et al 2002). [It is likely that the SPL is involved in relational (and rule) encoding as well as item but to a lesser extent, because relational information can be converted into an abstract format.]…”
Section: Discussionsupporting
confidence: 89%
“…An earlier study from our lab found a very similar area selectively activated for the updating of rule (compared with item) information in working memory [Montojo and Courtney 2008;see also Brass and von Cramon (2004) for more evidence that this region is implicated in updating of task rules]. Whereas we could not decode the representational content of relations in this region in the current study, the close concordance between the two studies suggests at least that there may be commonalities between rule and relational processing that recruit this region.…”
Section: Discussionmentioning
confidence: 71%
“…This finding underlines the crucial role of dlPFC in driving functional integration in the WM network. This is in line with a recent fMRI study demonstrating that rule updating preferentially activates prefrontal cortex and stimulus updating activates PC in healthy participants (Montojo and Courtney, 2008). The n-back task used in our study requires participants to update rules, 2-back versus 0-back, as well as continuous stimulus updating of numbers presented within each block.…”
Section: Prefrontal Activation and Cognitive Performancesupporting
confidence: 88%
“…It is thus unlikely that this lPFC region is primarily involved in the short-term storage of memory set items, but instead is more related to maintenance of goal-related information needed for successful performance, such as task sets or rules (29). Indeed, recent empirical work has suggested that lateral PFC is preferentially involved in active maintenance of goal-related information (30)(31)(32)(33)(34)(35). Interestingly, PFC neurons also code information related to the reward context (3,7,36).…”
Section: Discussionmentioning
confidence: 99%